Analisis Pertanyaan dalam Buku Ajar Bahasa Indonesia Tingkat Perguruan Tinggi Berdasarkan Taksonomi Bloom - Ardiyati, Syafira Mahfuzi; Sudewi, Ni Ketut Putri Nila (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to describe reading questions contained in textbooks Indonesian the university level using the cognitive dimension of Bloom's Taxonomy. This study used qualitative descriptive method. The data collection technique carried out in this study is in the form of documentation. The results showed that (1) there were 102 questions that were spread unevenly. (2) Bloom's taxonomy includes six cognitive domains namely C1 (remembering), C2 (understanding), C3 (applying), C4 (analyzing), C5 (judging), and C6 (creating). (3) Questions contained in textbooks Indonesian the college level of the cognitive realm understand /C2 dominates with a much greater percentage proportion than other cognitive levels